Three-component reactions of conjugated dienes, CH acids and formaldehyde under diffusion mixing conditions - Shybanov, Dmitry E.; Kukushkin, Maxim E.; Babaev, Eugene V.; Zyk, Nikolai V.; Beloglazkina, Elena K. (Beilstein Journal of Organic Chemistry, 2025)
A diffusion mixing technique with a volatile reagent was successfully used to generate crotonic condensation adducts of active methylene compounds and formaldehyde at room temperature in the absence of strong acids and bases. The formed adducts were highly reactive intermediates capable of reacting with dienes in a three-component reaction, leading to the formation of Diels–Alder main reaction products.
Keywords: aldol condensation; [4 + 2]-cycloaddition; diffusion mixing; formaldehyde; Knoevenagel condensation; three-component reactions